INFLUENCE OF PERSONALISATION ON MOBILE LOYALTY PROGRAMME CONFIRMATION AMONG RETAIL CONSUMERS IN SOUTH AFRICAN TOWNSHIPS - Mahlangu, Eva Nkgome (Economic Review: Journal of Economics and Business, 2025)
This study investigated the influence of personalisation benefits on the confirmation of mobile loyalty programmes among retail consumers in South African township markets. A quantitative research design was employed using an online self-administered survey. Data were collected from 516 black consumers, aged 18-65, residing in South African townships, who had used at least one mobile loyalty programme in the retail industry. Simple random sampling was used, and data were analysed using SmartPLS 4 for structural equation modelling. Demographic characteristics (education, gender, age, and income) were included as control factors. The results revealed that personalisation benefits have a significant but weak positive influence on confirmation. Gender, age, income, and education had no significant effects on confirmation. The study highlights the need for retailers to design and implement personalised mobile loyalty programmes that are tailored to consumers in township markets. This approach is crucial in strengthening consumers’ confirmation of mobile loyalty programmes and ultimately enhancing long-term programme use. The findings offer valuable insights into the under-researched township market and thus provide more understanding of mobile loyalty programme behavior. Additionally, the study extends the application of technology continuance theory and social exchange theory in a developing country context, adding value to academic literature. The study further adds value by adapting and validating measurement instruments for new, under-researched settings, which supports future research and instrument development in similar contexts.